2015
DOI: 10.1158/1078-0432.ccr-14-2779
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Trial of Combined BRAF and EGFR Inhibition in BRAF-Mutant Metastatic Colorectal Cancer Patients

Abstract: Purpose BRAF mutant metastatic colorectal cancer (mCRC) forms an aggressive subset of colorectal cancer with minimal response to selective RAF inhibitors. Preclinical data show that reactivation of epidermal growth factor receptor (EGFR) signaling occurs in colorectal tumor cells treated with RAF inhibitors and that the addition of an EGFR inhibitor enhances antitumor activity. These data suggest that combined therapy with RAF and EGFR inhibitors could be an effective strategy for treating BRAF V600E mCRC. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
172
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(177 citation statements)
references
References 39 publications
4
172
0
1
Order By: Relevance
“…At present, most suggestion of benefit from targeted therapy in gastric carcinoma is guided by analogy to other tumor types. Such reasoning highlights the limitations of this approach, for example, BRAF V600E-mutant colorectal www.TheOncologist.com adenocarcinoma has not suggested benefit from vemurafenib monotherapy [53,54]. Because new approaches such as the combination of vemurafenib and erlotinib confer some benefit to similar patients, as noted, it is hoped that analogous approaches can also benefit gastric carcinoma patients [54].…”
Section: Clinical Genomic Profiling In Gastric Cancermentioning
confidence: 99%
“…At present, most suggestion of benefit from targeted therapy in gastric carcinoma is guided by analogy to other tumor types. Such reasoning highlights the limitations of this approach, for example, BRAF V600E-mutant colorectal www.TheOncologist.com adenocarcinoma has not suggested benefit from vemurafenib monotherapy [53,54]. Because new approaches such as the combination of vemurafenib and erlotinib confer some benefit to similar patients, as noted, it is hoped that analogous approaches can also benefit gastric carcinoma patients [54].…”
Section: Clinical Genomic Profiling In Gastric Cancermentioning
confidence: 99%
“…These responses, however, have been transient, with median progression-free survival of 3.2 months (95% CI: 1.6-5.3 months). 27 Preliminary findings from another study and a case report evaluating cetuximab and vemurafenib demonstrated similar results. 52,53 Preliminary findings from other studies have also noted modest activity with combination therapies targeting EGFR, BRAF, and MEK.…”
mentioning
confidence: 67%
“…1,[24][25][26] In CRC, BRAF mutations have been found to be mutually exclusive with RAS mutations. 23,27 Additionally, the pattern of metastatic spread at diagnosis appears unique in this patient population compared to that in patients with BRAF-WT tumors. Liver involvement at the time of diagnosis was less common (60% vs 80%, P,0.01), and peritoneal involvement was more common (26% vs 14%, P,0.01).…”
Section: Braf In Crc Clinical and Pathologic Features Of Patients Witmentioning
confidence: 95%
See 1 more Smart Citation
“…MEK inhibitors can enhance T-cell function and improve checkpoint blockade as demonstrated in murine melanoma models (44). Clinical studies are investigating combinations between these inhibitors as well as with other modalities (45,46). Data from a trial using atezolizumab in combination with the MEK inhibitor cobimetinib show the combination was well tolerated, and patients had an ORR of 17% (4 PR and 5 SD;ref.…”
Section: Pd-(l)1 Inhibitor Nonrespondersmentioning
confidence: 99%